Prevention of post dural puncture headache in Saudi Arabia - Albanna, Alanoud K.; Alnefaie, Zayed M.; Alhawsawi, Mawaddah O.; Almuwallad, Ayah A. (International Journal Of Community Medicine And Public Health, 2025)
Post-dural puncture headache (PDPH) is a common complication following lumbar puncture procedures. It can lead to significant discomfort, functional impairment, and prolonged recovery, especially among female patients, younger individuals, and those with low body mass index (BMI) or a prior history of headaches. This review aims to synthesize current evidence on the etiology, risk factors, prevention, and treatment of PDPH, with a focus on clinical practices in Saudi Arabia. A narrative literature review was conducted using databases such as PubMed, Google Scholar, and ScienceDirect. Studies were selected based on their relevance to PDPH diagnosis, management, and outcomes, with a focus on peer-reviewed articles published in the past five years. Effective prevention includes the use of smaller, non-cutting spinal needles and optimal patient positioning during lumbar puncture. While conservative treatments like hydration and analgesia offer limited relief, the epidural blood patch (EBP) remains the most effective therapeutic option, particularly when administered within 48 hours of symptom onset. The variability in protocol adherence across Saudi institutions suggests a need for national clinical guidelines. Implementing standardized practices and early intervention strategies can substantially reduce the burden of PDPH in Saudi Arabia. Further region-specific research and healthcare provider training are essential to improve patient outcomes and minimize procedural complications.